The association between neutrophil to lymphocyte ratio and contrast induced nephropathy in patients with ST segment elevation myocardial infarction (Annals of Medical Research, 2021)
Aim: The increase in the number of percutaneous coronary interventions(PCI) has also led to an increase in risk associated with intervention-including radiation injury, contrast-induced nephropathy (CIN), risk of stroke, and vascular complications. The development of CIN is an important clinical situation in patients undergoing PCI. In this study we aimed to investigate the association between inflammatory parameters and CIN development in patients with ST segment elevation myocardial infarction (STEMI).Material and Methods: Patients who underwent coronary angiography with STEMI diagnosis between January 2015 and March 2018 were included in the study. Two groups were formed according to the CIN status and predictors of CIN were investigated. Results: The average age of the patients is 58±12 years and 78.2% males. In multivariate analysis, NLR (OR: 0.92, 95% CI: 0.86-0.98 and p: 0,022) and Lesion length (OR: 0.88, 95% CI: 0.79-0.98 and p: 0,029)and were associated with CIN development. Conclusions: In this study, we showed that lesion length and NLR were independent predictors of CIN and we proposed that inflammatory process could play key role in CIN development when compared to traditional risk factors. Keywords: Neutrophil to lymphocyte ratio; coronary artery disease; contrast-induced nephropathy; propensity score matching.
Keywords: key role in CIN development when compared to traditional risk factors. br / Neutrophil to lymphocyte ratio; coronary artery disease; contrast-induced nephropathy; propensity score matching.